Dzyaloshinskii–Moriya interaction induced domain wall depinning anomaly in ferromagnetic nanowire - Teoh, Han Kheng (2017)
Magnetic domain wall positional manipulation is usually through the introduction of potential trap. In this work, we show that the presence of interfacial Dzyaloshinkii–Moriya interaction leads to a different static depinning field for Néel domain walls with the same handedness in a notched magnetic nanowire. The difference in static depinning field is due to the Néel domain wall spin orientation. The spin orientation leads to different torques being exerted on the localized magnetic moments. This inherently imposes a spin orientation dependent diode-like behavior for domain walls in a notched nanowire. An equation which relates the difference in static depinning field to the notch geometry is derived. Micromagnetic simulation with varying damping constant reveals the influence of damping constant on the strength of depinning anomaly.